2014
DOI: 10.4067/s0718-16202014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vis-Nirs for Land Management Classification With a Support Vector Machine and Prediction of Soil Organic Carbon and Other Soil Properties

Abstract: G. Debaene, D. Pikuła, and J. Niedźwiecki. 2014. Use of VIS-NIRS for land management classification with a support vector machine and prediction of soil organic carbon and other soil properties. Cien. Inv. Agr. 41(1): 21-32. The objective of this research was to investigate the effects of a long-term experiment on soil spectral properties and to develop prediction models of these properties (soil organic carbon (SOC), N, pH, Hh, P 2 O 5 , K 2 O, Ca, Mg, K, and Na content) from texturally homogeneous samples (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It was successfully used for the quantitative analysis of a variety of physical and chemical soil properties such as moisture, total C, N and P content, quality of organic matter, etc. [ 20 , 23 ], and soil biological parameters such as respiration, microbial biomass, potential mineralization of N and ratio of microbial C to organic C [ 18 ]. VIS-NIR spectroscopy is gradually becoming more popular for the rapid screening of contaminants in soils as more recent studies have demonstrated its efficacy in the detection of heavy metals (Cd, Pb, Cu, Zn) [ 24 , 25 ], total and bioavailable PAHs [ 12 , 26 , 27 , 28 ], individual compounds, e.g., benzo[a]pyrene [ 12 ] or phenanthrene [ 29 ], and total petroleum hydrocarbons [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was successfully used for the quantitative analysis of a variety of physical and chemical soil properties such as moisture, total C, N and P content, quality of organic matter, etc. [ 20 , 23 ], and soil biological parameters such as respiration, microbial biomass, potential mineralization of N and ratio of microbial C to organic C [ 18 ]. VIS-NIR spectroscopy is gradually becoming more popular for the rapid screening of contaminants in soils as more recent studies have demonstrated its efficacy in the detection of heavy metals (Cd, Pb, Cu, Zn) [ 24 , 25 ], total and bioavailable PAHs [ 12 , 26 , 27 , 28 ], individual compounds, e.g., benzo[a]pyrene [ 12 ] or phenanthrene [ 29 ], and total petroleum hydrocarbons [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a higher SOC content means a lower reflectance but this is not the case here. This is probably due to differences in soil texture having a significant impact on spectra (Debaene et al 2014;Hermansen et al 2017). The small peak observed in natural soils at 390 nm can be attributed to humic acids (Ouatmane et al 2000).…”
Section: Effect Of Ercm-biochar Application On Soil Spectral Propertiesmentioning
confidence: 99%
“…there is more variability in medium soc content spectra probably due to the mixing of the top soil with deeper layers. the spectra are clearly related to the soc content in that example since the soil textures are similar (table 1) and, therefore, have no effect on the spectral characteristics (Debaene et al 2014b). the reflectance for the low soc content samples in the 400-1,000 nm range has a different shape since that region of the spectra is influenced by the soc content.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near-infrared (Vis-nir) spectroscopy is regarded as an efficient technology to investigate soils for various purposes like soil monitoring, soil mapping, and precision agriculture (Debaene et al 2014b(Debaene et al , stenberg et al 2010). the method is based on the absorption by the soil constituents of the near-infrared radiation by different chemical bonds such as o-H, c-H, n-H, s-H and c=o.…”
Section: Introductionmentioning
confidence: 99%